2010
DOI: 10.4161/cbt.10.10.13248
|View full text |Cite
|
Sign up to set email alerts
|

The Axl receptor tyrosine kinase is an adverse prognostic factor and a therapeutic target in esophageal adenocarcinoma

Abstract: Esophageal adenocarcinoma (EAC) arises in the backdrop of reflux-induced metaplastic phenomenon known as Barrett esophagus. The prognosis of advanced EAC is dismal, and there is an urgent need for identifying molecular targets for therapy. Serial Analysis of Gene Expression (SAGE) was performed on metachronous mucosal biopsies from a patient who underwent progression to EAC during endoscopic surveillance. SAGE confirmed significant upregulation of Axl “tags” during the multistep progression of Barrett esophagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 34 publications
8
60
0
Order By: Relevance
“…Increased MER expression is associated with leukemias, lymphomas, melanoma, rhabdomyosarcomas, and gastric and prostate cancers (4)(5)(6). AXL and MER expression also has been directly correlated with poor prognosis in cancer (6)(7)(8)(9). Moreover, ectopic expression of AXL has been shown to confer resistance to EGF receptor therapy in lung cancer (10,11).…”
mentioning
confidence: 99%
“…Increased MER expression is associated with leukemias, lymphomas, melanoma, rhabdomyosarcomas, and gastric and prostate cancers (4)(5)(6). AXL and MER expression also has been directly correlated with poor prognosis in cancer (6)(7)(8)(9). Moreover, ectopic expression of AXL has been shown to confer resistance to EGF receptor therapy in lung cancer (10,11).…”
mentioning
confidence: 99%
“…Interestingly, gene expression analysis in prostate cancer cells treated with Anxa2 shows increase in expression of Axl which is also a tyrosine kinase receptor for GAS-6. Axl expression is correlated with metastasis and poor prognosis in a wide range of cancers such as breast cancer, prostate cancer, pancreatic cancer, ovarian cancer, renal cell carcinoma and esophageal adenocarcinoma [96][97][98][99][100]. Signaling through GAS-6 and its receptor Axl promotes invasion of prostate cancer cells towards the bone and regulates prostate cancer proliferation and survival [101].…”
Section: Chemotaxis Towards Bonementioning
confidence: 99%
“…We thus suggested a therapeutic approach for treating local advanced ESCC by considering serum levels of EGF and VEGF as biomarkers. AXL RTK has demonstrated potential to become a novel target for cancer targeted therapy, including in EAC (20). We recently demonstrated that patients positive for AXL in tumor tissue have increased risks of death and distant metastasis, and their median survival time dramatically decreased from about 47 to 14 months.…”
Section: Esophageal Cancermentioning
confidence: 99%